The Impact Of Pragmatic Considerations On Grammatical Formations “A Practical Study In Arabic And English” - Turkey Atiyah, Anwar (Opción, 2019)
The connection between grammatical formations and pragmatics reflects the ability to understand another speaker’s implicit meaning in a mechanism that is called pragmatic competence. In this context, the study aims at defining this pragmatic competence. In addition, it aims at clarifying and analyzing the connection between pragmatic considerations and grammatical formations through discussion and investigating the pragmatic objectives of the grammar of both English and Arabic language in the selected phrases that represent this connection in English and Arabic.